Italy : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report, 2020)
This 2020 Article IV Consultation with Italy reflects discussions with the Italian authorities in January 2020 and is based on the information available as of January 28, 2020. It focuses on Italy's medium-term challenges and policy priorities and was prepared prior to the outbreak of COVID-19 in Italy. It, therefore, does not cover the outbreak or the related policy response, which has since become the overarching near-term priority. The outbreak has greatly amplified uncertainty and downside risks around the outlook. Staff is closely monitoring this health crisis and will continue to work on assessing its impact and the related policy response in Italy and globally. The overarching challenges are to raise growth and enhance resilience. The IMF staff projects growth in Italy to be the lowest in the European Union over the next five years. High public debt remains a key source of vulnerability. Substantial progress has been made in strengthening bank balance sheets, but important weaknesses remain. In order to durably raise growth and reduce vulnerabilities, Italy needs faster potential growth and medium-term fiscal consolidation.